Ultrafast Electron Transfer Dynamics of Organic Polymer Nanoparticles with Graphene Oxide. Issue 22 (9th March 2023) - Li, Dong; He, Xiaoxiao; Zhao, Litao; Jia, Menghui; Li, Haoyang; Zhang, Sanjun; Zhang, Xiaolei; Chen, Jinquan; Jin, Qingyuan; Xu, Jianhua
Abstract: We prepared organic polymer poly‐3‐hexylthiophene (p3ht) nanoparticles (NPs) and graphene oxide (GO)/reduced graphene oxide (RGO) composites p3ht NPs‐GO/RGO by using the reprecipitation method. We demonstrated that GO/RGO could improve the ordering and planarity of p3ht chains as well as the formation of p3ht NPs, and confirmed the effects of GO/RGO on the fluorescence and carrier transport dynamics of p3ht NPs by using femtosecond fluorescence upconversion and transient absorption (TA) techniques. Ultrafast electron transfer (∼1 ps) between GO/RGO and p3ht NPs quenched the fluorescence of p3ht NPs, indicating excellent properties of p3ht NPs‐GO/RGO as the charge transfer complexes. Efficient electron transfer may promote the applications of p3ht NPs‐GO/RGO composites in organic polymer solar cells and photocatalysis. Moreover, RGO had stronger interfacial interactions and more matched conduction band energy levels with p3ht NPs than GO did, which implied that p3ht NPs‐RGO might have greater application values than p3ht NPs‐GO. Abstract : Poly‐3‐hexylthiophene nanoparticles with graphene oxide (p3ht NPs‐GO & p3ht NPs‐RGO) were prepared, and revealed the properties of charge transfer complexes. Notably, ultrafast electron transfer in those composites was reported for the first time, and faster electron transfer in p3ht NPs‐RGO implied that p3ht NPs‐RGO might have higher application values for organic polymer solar cells.